Lokalitas Konten dalam Visual Kaos Cak-Cuk Surabaya - Arjuna Bangsawan (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2014)
In the realm of fashion, t-shirt has a basic function in man dressed as a complement. As it grows a shift in the value of the function t-shirts. In addition to functioning as a complement to dress, t-shirts can be used as a medium of communication, conveys criticism, existence, identity portrayal, as well as a means of identity and promotion. Kaos Cak Cuk Surabaya is one of the local T-shirt original regional Surabaya Suroboyoan consistent use in displaying visual culture. Through the language of visual pun and parody are blasted with locality Surabaya, Surabaya Cak Cuk in her locality brings humor and antics.